Numerical simulation of waves overtopping over impermeable sloped seadikes. (15th December 2022) - Sharifian, Mahdi; Moghim, Mohammad Navid; Chamani, Mohammad Reza
Abstract: In this study, a numerical model of white water overtopping of regular waves over an impermeable seadike is developed using the Volume of Fluid (VOF) method based on Reynolds-Averaged Navier-Stokes (RANS). The numerical model is favored due to the challenges in experimentally quantifying the hydrodynamic features of overtopping flow, particularly at the beginning of the crest, as well as the uncertainty in various design formulae estimating wave overtopping rates. Such uncertainties are caused by insufficient wave height statistics in irregular wave trains, which may be addressed by taking into account overtopping rates of regular wave tests as well as robust statistical distributions of wave heights and periods. For this purpose, first, by ensuring the numerical model's validity, effective hydraulic and structural parameters on regular waves overtopping are investigated and their dimensionless forms are determined using the dimensional analysis method. Based upon the developed model and in-depth estimation of dimensionless parameters' effect on overtopped layer thickness, the overtopping velocity at the beginning of the crest, and the average overtopping rate, the wave breaker type is determined to be highly effective at reducing overtopping parameters. By analyzing the numerical model run results, formulae are proposed to predict the layer thickness, the wave overtopping velocity at the beginning of the crest, and the average wave overtopping rate independent of the flow characteristics on the slope seaward. Comparing the results of the proposed formulae with other researchers highlights the appositeness and reliability of the numerical simulation and the proposed formulae. Using the obtained formulae of layer thickness and overtopping velocity, along with consideration of sliding, toppling, and floating criteria, appropriate criteria are proposed to control the overtopping safety for pedestrians and vehicles. Moreover, compared to the average overtopping rate, the overtopping velocity and layer thickness parameters are found to be more appropriate in investigating the overtopping risk for pedestrians and vehicles. Highlights: A numerical model of white water overtopping of regular waves over an impermeable seadike is developed. Based on the developed model, the wave breaker type is determined highly effective at reducing overtopping parameters. The formulae are proposed to predict the overtopping parameter independent of the flow characteristics on the slope seaward. The overtopping velocity and layer thickness parameters are found to be more appropriate to investigate the overtopping risk for pedestrians and vehicles.